(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Particles pre - equilibrium spectra and angular distribution are calculated by usingFeshbach-Kerman- Koonin (FKK) model with PRECO-2006 code. The angular distribution of the nuclei of nuclear reactions between the nucleus of a target (90Zr) and the tapline of light particles wascalculated by using reactions of the multistep compound (MSC) and of multistep direct (MSD).Isospin, the finite well depth, and shell effects are considered. Byusing [(_40^90)〖Zr〗_50 ] as target material the cross section of [90Zr(n,n)90Zr], [90Zr(n,p)90Y], [90Zr(n,D)89Y], [90Zr(n,T)88Y], [90Zr(n,3He)88Sr] and [90Zr(n,4He)87Sr] reactions were estimated. Values of cross sections estimated are 550, 371, 16.3, 4.55, 0.271 and 2.35 mb/MeV respectively. Also the angular distribution of same nuclear reactions were estimated, and the values of angular distribution are 850, 392, 4.55, 4.55,0.27 and 2.35mb/sr.MeV respectively.